Performing percutaneous nephrolithotomy under modified local anesthesia - Yu, Yue; Hu, Jieping; Liu, Wei; Peng, Zhixiong; Wang, Mengzhen; Zhou, Xiaochen; Xi, Haibo (Frontiers in Surgery, 2022)
Objective: This pilot study was aimed to assess the practicability and effectiveness of modified local anesthesia (m-LA) for patients undergoing percutaneous nephrolithotomy (PCNL). Methods: PCNL under m-LA was performed in 83 patients between Nov 2020 to May 2021. For LA, 1% lidocaine 10 ml and ropivacaine hydrochloride 10 ml were mixed and instilled under ultrasound guidance through the percutaneous nephrolithotomy channel directed towards the design calix. 18F or 20F ClearPetra Nephrostomy Sheath was used in surgery to keep low pressure in renal pelvis. Demographic characteristics, stone characteristics, Visual Analogue Scale (VAS) score, vital signs, operation time, complications, and stone clear rate were recorded and analyzed. Results: All operations were successfully completed. The mean VAS score was 3.9±1.0. The mean operation time was 55.1±23.6 min. The changes for systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate was 3±21mmHg, 1±14mmHg, and -6±14 beats/min, respectively. The change for hemoglobin was -10.7±10.9 g/L. Change for C-reactive protein was 5.39±43.1 mg/L. Total stone free rate was 69.9% (93.8% for simple stones and 54.9% for complex stones). Conclusion: Performing PCNL under modified local anesthesia under ultrasound guidance was found to be strongly practical and effective.